2019
DOI: 10.1111/tpj.14423
|View full text |Cite
|
Sign up to set email alerts
|

Chloride as a macronutrient increases water‐use efficiency by anatomically driven reduced stomatal conductance and increased mesophyll diffusion to CO2

Abstract: Summary Chloride (Cl−) has been recently described as a beneficial macronutrient, playing specific roles in promoting plant growth and water‐use efficiency (WUE). However, it is still unclear how Cl− could be beneficial, especially in comparison with nitrate (NO3−), an essential source of nitrogen that shares with Cl− similar physical and osmotic properties, as well as common transport mechanisms. In tobacco plants, macronutrient levels of Cl− specifically reduce stomatal conductance (gs) without a concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 112 publications
2
64
0
Order By: Relevance
“…We employed chlorine concentrations that were not expected to induce visible toxicity symptoms (e.g., chlorosis, leaf tip burning, stunting, etc.) [28]. In addition to an anion-anion competition, the linear decrease of the nitrate concentration from highest to intermediate NS ratios is likely to be due also to the chloride interference with several steps of nitrogen utilization (e.g., uptake, assimilation, translocation and remobilization).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed chlorine concentrations that were not expected to induce visible toxicity symptoms (e.g., chlorosis, leaf tip burning, stunting, etc.) [28]. In addition to an anion-anion competition, the linear decrease of the nitrate concentration from highest to intermediate NS ratios is likely to be due also to the chloride interference with several steps of nitrogen utilization (e.g., uptake, assimilation, translocation and remobilization).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the interplay between these signal molecules involves a number of plant functions, and therefore, the crosstalk between the nitrate, NO and phytohormones signaling pathways chains the multifaceted and complex metabolomic signatures we observed [46,[54][55][56] In conclusion, our work indicated that the interplay between nitrates and chlorines exerts a large effect on basil yield and metabolomic profile, that cannot be satisfactorily explained only by an anion-anion antagonist outcome (e.g., a replacement effects and carrier competition processes). Considerable changes were observed in a number of chemical classes and their relation with the different nutrient ratios suggests a dose-dependent effect that is mainly the combination of a response to nutrient availability (e.g., primarily nitrogen) [56] and an inducible response to stress, which is evident when chloride concentration in the nutrient solution exceeds that which is capable to satisfy nutrient requirements [28]. Our work highlighted the potential and the magnitude of the effect of NS management for leafy vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that osmotic effects of the Cl − dominant solution on leaf expansion and light interception were not prominent and the differences in plant dry mass between the control and Cl − dominant treatment mainly resulted from the osmotic effects on leaf photosynthesis, which reduced photosynthesis rate by 13% and 11% in Aramon and Line-759, respectively, according to the value of O s in Equations (2) and (3). Since Cl − can be used by the plant as an osmoregulator to promote leaf expansion, the insignificant difference in total leaf area between the control and Cl − dominant solution was probably a counterbalance between the negative effects of osmotic stress and the positive effects of Cl − on leaf cell expansion [36,37]. It is also interesting that cucumber seems to have mechanisms avoiding overaccumulation of Cl − .…”
Section: Pumpkin Improved Photosynthesis and Regulated Ion Distributimentioning
confidence: 99%
“…The beneficial effect of macronutrient Clnutrition in maintaining high photosynthesis rates while improving WUE is particularly challenging in C 3 plants, in which water loss through transpiration is inherent to the process of fixing atmospheric CO 2 . This is because Clspecifically increases the mesophyll diffusion conductance to CO 2 (Franco-Navarro et al, 2019;Maron, 2019). This is a consequence, at least in part, of a higher surface area of chloroplasts exposed to the intercellular airspace of mesophyll cells.…”
Section: Chloride Membrane Transportmentioning
confidence: 99%